Color and power Doppler sonography - Jeffrey, R. Brooke; Medical Interactive (Firm) ([New York] : Lippincott-Raven, 1997)
(Producer) A guide to the clinical use of color Doppler and power Doppler ultrasound. It contains 125 illustrated clinical cases that highlight the diagnostic capability of color and power Doppler and demonstrate how to perform the examination and interpret the results. The cases cover a wide variety of common clinical entities, including vascular, abdominal, pelvic, and endocavity disorders, as well as small parts ultrasound and interventional sonography. Contains 500 scans, including 450 in full color
'Software version 1.0'--Accompanying disk label
Accompanying computer disk contains the Macintosh version of the CD-ROM software
Editors : R. Brooke Jeffrey, Jr., Philip W. Ralls
System requirements for optical disc: IBM or compatible 486 computer; 4 Meg memory; Windows 95 or Windows 3.1; 256 col. VGA card; CD-ROM drive
System requirements for magnetic disk: Macintosh computer
Keywords: Ultrasonography, doppler, color